Design & modelling of absorption cooling system integrated with solar thermal storage: utilizing solar energy for cooling of an educational building in Pakistan using TRNSYS - Iftikhar Bashir Butt (00000204920); Dr. Adeel Waqas (USPCAS-E, NUST, Islamabad, 2020)
TH-211
Keywords: MS-ESE Thesis MS Thesis